2002
DOI: 10.3354/meps225097
|View full text |Cite
|
Sign up to set email alerts
|

Sieve size influence in estimating biomass, abundance and diversity in samples of deep-sea macrobenthos

Abstract: A divergence in sieve size protocols for washing samples has arisen among shallow-and deep-sea benthic biologists, which now affects comparability across the 2 environments. This has come about as a result of a perception of smaller body size among deep-sea benthic organisms. Two box-core samples from ~1900 m depth were examined to see how different sieve size affects estimation of biomass, abundance and diversity of macrofauna in the deep sea. Expressed as cumulative retentions, the coarsest sieve (1 mm mesh)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
52
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(59 citation statements)
references
References 48 publications
7
52
0
Order By: Relevance
“…The macrofauna includes a highly diverse group dominated by polychaete worms, peracarid crustaceans and mollusks. The type of quantitative sampling gear deployed and the sieve mesh size affect estimates of standing stock in the meiofauna and macrofauna (Bett et al 1994, Gage et al 2002. We tested for their potential influence by using partial regression.…”
Section: Methodsmentioning
confidence: 99%
“…The macrofauna includes a highly diverse group dominated by polychaete worms, peracarid crustaceans and mollusks. The type of quantitative sampling gear deployed and the sieve mesh size affect estimates of standing stock in the meiofauna and macrofauna (Bett et al 1994, Gage et al 2002. We tested for their potential influence by using partial regression.…”
Section: Methodsmentioning
confidence: 99%
“…North Atlantic) often do not publish associated environmental data. All studies used a sieve size of 0.3 or 0.5 mm, a size that captures the majority of macrofaunal diversity [29] (77 stations used a 0.3 mm sieve and 17 stations used a 0.5 mm sieve). We note that the area of seafloor sampled at each station differs between studies and even within studies (electronic supplementary material, dataset 1), which could differentially affect the accuracy of reported diversity metrics [30].…”
Section: Materials and Methods (A) Dataset Assemblymentioning
confidence: 99%
“…Gage et al (2002) mentioned that diVerences between sieving a sample alive or after Wxation, might occur in samples from shallow water, where the movement or posture of living animals may aVect the operation of the sieve, but this would not normally occur within deep sea samples because the animals are generally dead by the time they reach the surface.…”
Section: Impacts At the Density Levelmentioning
confidence: 99%
“…This bias in sieving procedure can be largely assigned to the choice between the retention of as much species and individuals as possible (sieving after Wxation) and the avoidance of environmental contamination with large volumes of formalin (sieving alive). While numerous authors mentioned that, for certain species, an actual impact of sieving procedure should be expected (Thorson 1957;Govaere 1978;Bilyard et al 1987;Bachelet 1990;Rumohr 1990;Gage et al 2002;Van Hoey et al 2004), little research was done on the qualiWcation and quantiWcation of the diVerence in sieving procedure. In his study on the eVect or sieving procedure on the benthos retained with a 0.5 mm mesh sized sieve, Ohwada (1988) reported that polychaetes might be far more abundant (up to 20 times) in samples sieved after Wxation compared to samples sieved alive.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation